The Influence of Price and Product Quality on Repurchase Decision with Consumer Satisfaction as a Mediation Variable - Erick Prafitra Aldiki; Luk Luk Atul Hidayati; Friztina Anisa (Urecol Journal. Part B: Economics and Business, 2022)
The purpose of this study was to determine the relationship between price and product quality on repurchase decisions with consumer satisfaction as a mediating variable. The sample used in this study were consumers at Dam Coffee House & Eatery, Magelang Regency. The sampling method is Accidental Sampling with 100 respondents. The analysis tool uses multiple regression with the help of SPSS 26.0 software. The results show that price has a positive effect on repurchase decisions, product quality has a positive effect on repurchase decisions, price has a positive effect on consumer satisfaction, product quality has a negative effect on consumer satisfaction, consumer satisfaction has a positive effect on repurchase decisions, consumer satisfaction mediates the relationship between price and repurchase decisions, consumer satisfaction mediates the relationship between product quality and repurchase decisions.